Pachypodostyflavone, a New 3-methoxy Flavone and Other Constituents with Antifilarial Activities from the Stem Bark of Duguetia staudtii - Mbobda, Alexis Sylvain Wafo; Ngouonpe, Alain Wembe; Happi, Gervais Mouthé; Mountessou, Bel Youssouf G.; Monya, Elvis; Jouda, Jean-Bosco; Toussie, Billy Tchegnitegni; Lenta, Bruno Ndjakou; Sewald, Norbert; Kouam, Simeon Fogue; Tchouankeu, Jean Claude (Planta Medica International Open, 2021)
A new flavone derivative named pachypodostyflavone (1), along with 8 known compounds (2–9) and a mixture of β-sitosterol and stigmasterol were isolated from the stem bark of Duguetia staudtii (Annonaceae), based on a bioassay-guided fractionation. Their structures were determined using high-resolution mass spectrometry and NMR spectroscopic data, as well as by comparison with the literature values of their analogs. Selected isolated compounds were evaluated for their in vitro antifilaricidal activities on Onchocerca ochengi microfilariae and adult worms. Inhibition of motility was evaluated spectroscopically on microfilaria and adult male worms. Viability was determined on adult female worms by the MTT/ Formazan assay. Auranofin at 10 µM and 2% DMSO were used as positive and negative controls, respectively. Compounds 1 and 7 showed potent anti-onchocerca activities with 100% activity at 250 µg/mL on both O. ochengi adult male and female worms, while compound 5 displayed 100% activity at 30 µg/mL.
Keywords: Duguetia staudtii; Annonaceae; bio-guided fractionation; flavone; pachypodostyflavone; antifilarial activity; Onchocerca ochengi microfilariae